Exploring the Role of HRM in Facilitating Collaboration and Knowledge Sharing in Decentralized Organizational Structures - Liwang, Asmita Wulansari Dg. (Management Studies and Business Journal (PRODUCTIVITY), 2024)
This research investigates the role of human resources (HR) in facilitating collaboration and knowledge sharing in decentralized organizational structures. Through a systematic literature review approach, this study collects and analyzes various relevant literature from international databases. The research results highlight the importance of collaborative leadership, awareness, and organization of inter-organizational processes in facilitating collaboration in decentralized contexts. Additionally, factors such as individual motivation, management support, and technology also influence knowledge sharing practices within organizations. Empirical studies confirm that decentralized structures play an important role in facilitating collaboration and knowledge sharing, which in turn improves organizational performance and innovation. In conclusion, a deeper understanding of the dynamics of collaboration and knowledge sharing in decentralized structures has important implications for human resource management and organizational development.